derivative of inverse
The derivative of the inverse of a function is given by the formula:
d/dx (f^(-1)(x)) = 1 / (dy/dx)_x
Here, f^(-1)(x) represents the inverse function of f(x), and (dy/dx)_x represents the derivative of the original function f(x) evaluated at the point x
The derivative of the inverse of a function is given by the formula:
d/dx (f^(-1)(x)) = 1 / (dy/dx)_x
Here, f^(-1)(x) represents the inverse function of f(x), and (dy/dx)_x represents the derivative of the original function f(x) evaluated at the point x.
To prove this formula, we can use the definition of the derivative:
(d/dx (f^(-1)(x))) = lim (h -> 0) [(f^(-1)(x + h) – f^(-1)(x)) / h]
Let y = f^(-1)(x), then we have x = f(y). Now, let’s differentiate both sides with respect to x:
d/dx (x) = d/dx (f(y))
1 = dy/dx
Now, we can rewrite the expression from the definition of the derivative using y instead of f^(-1)(x):
(d/dx (f^(-1)(x))) = lim (h -> 0) [(y + h – y) / h]
Simplifying, we get:
(d/dx (f^(-1)(x))) = lim (h -> 0) (h / h)
(d/dx (f^(-1)(x))) = lim (h -> 0) 1
(d/dx (f^(-1)(x))) = 1
Thus, we have shown that the derivative of the inverse function is equal to 1, which matches the formula stated at the beginning.
More Answers:
Discover the Power of Arctan(x): Unlocking Angles and Tangents in MathematicsUnderstanding the Arcsin Function: Finding Angles in Right Triangles based on Ratios
Understanding the Arccos Function: Definition, Usage, and Examples